Electricity metering equipment (a.c.). Acceptance inspection. Particular requirements for static meters for active energy (classes 0, 2 S, 0, 5 S, 1 and 2, and class indexes A, B and C) Part 31, (30th September 2010) - British Standards Institution,
No abstract available